Great Queer Provocation: The Seriously Playful Recognition Game - Goessl, Martin J (transcript Verlag, 2024)
Queer cultures are vibrant components of the constantly transforming societies of the 21st century. This is both socially and anthropologically recognizable, as well as individually readable. Categories such as wealth, success, amusement, but also sexuality and beauty have undergone major changes within queer subcultures and have influenced the reality of life for the general public. The entanglements in heteronormative systems and capitalist orders are increasingly putting a queer point of view under pressure, so that the question seems justified: What makes someone or something queer? Queere Kulturen sind lebendige Bestandteile von sich stetig transformierende Gesellschaften des 21. Jahrhunderts. Dies ist sowohl sozial-anthropologisch erkennbar, als auch individuell ablesbar. Kategorien wie Wohlstand, Erfolg, Amüsement, aber auch Sexualität und Schönheit haben innerhalb queerer Subkulturen eine starke Veränderung erfahren und gleichsam so manche Lebensrealität einer allgemeinen Öffentlichkeit beeinflusst. Die Verstrickungen in heteronormative Systeme und kapitalistische Ordnungen bringen einen queeren Standpunkt zunehmend in Bedrängnis, sodass die Frage berechtigt erscheint: Was macht jemanden oder etwas queer?